George F. Becker papers - Becker, George F. (George Ferdinand), 1847-1919.
Correspondence, memoranda, letterbooks, diaries, notes, notebooks, reports, articles, charts, tables, blueprints, maps, landscape sketches, memorabilia, printed matter, and other papers relating primarily to Becker's service as geologist-in-charge, U.S. Geological Survey. Documents his geological investigations in Nevada, southern Alaska, South Africa, the Pacific slope, and the Philippines. Also documents his service as geophysicist of the Carnegie Institution of Washington, 1898; U.S. representative at the Radioactivity Congress in Brussels, Belgium, in 1910; and president of the Geological Society of America, 1914. Correspondents include Andreas Arzruni, James Franklin Bell, Theodore E. Burton, William Crozier, Edward Salisbury Dana, James Dwight Dana, Samuel Franklin Emmons, Archibald Geikie, A. Hague, Eugene W. Hilgard, Edmund Otis Hovey, Henry Marion Howe, Louis Janin, Waldemar Lindgren, Charles Washington Merrill, Simon Newcomb, Charles S. Peirce, Chester W. Purington, Theodore Roosevelt, H.W. Turner, Charles D. Walcott, and Robert Simpson Woodward.
Library of Congress Prints and Photographs Division.
Geologist, mathematician, engineer, and physicist.
Collection material in English, with Spanish and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Arzruni, Andreas, -- 1847-1898 -- Correspondence; Bell, James Franklin, -- 1856-1919 -- Correspondence; Burton, Theodore E. -- 1851-1929 -- Correspondence; Crozier, William, -- 1855-1942 -- Correspondence; Dana, Edward Salisbury, -- 1849-1935 -- Correspondence; Dana, James Dwight, -- 1813-1895 -- Correspondence; Emmons, Samuel Franklin, -- 1841-1911 -- Correspondence; Geikie, Archibald, -- 1835-1924 -- Correspondence; Hague, A. -- 1840-1917 -- Correspondence; Hilgard, Eugene W. -- 1833-1916 -- Correspondence; Hovey, Edmund Otis, -- 1862-1924 -- Correspondence; Howe, Henry Marion, -- 1848-1922 -- Correspondence; Janin, Louis, -- 1837-1914 -- Correspondence; Lindgren, Waldemar, -- 1860-1939 -- Correspondence; Merrill, Charles Washington, -- 1869-1956 -- Correspondence; Newcomb, Simon, -- 1835-1909 -- Correspondence; Peirce, Charles S. -- 1839-1914 -- Correspondence; Purington, Chester Wells, -- 1871- -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Turner, H. W. -- 1857- -- Correspondence; Walcott, Charles D. -- 1850-1927 -- Correspondence; Woodward, Robert Simpson, -- 1849-1924 -- Correspondence; Becker family; Carnegie Institution of Washington; Geological Society of America; Geological Survey (U.S.); Geology -- Alaska; Geology -- Nevada; Geology -- North America; Geology -- Pacific Coast (America); Geology -- Philippines; Geology -- South Africa; Geology -- United States; Geology -- United States -- Societies, etc; Geophysics; Radioactivity -- Congresses; Geologists; Mathematicians; Physicists; Scientists